Transdiagnostic Effects of Schizophrenia Polygenic Scores on Treatment Outcomes in Major Psychiatric Disorders - Serretti A; Baune BT (Neuropsychiatric Disease and Treatment)
Alessandro Serretti,1,2 Bernhard T Baune3– 5 1Department of Medicine and Surgery, Kore University of Enna, Enna, Italy; 2Oasi Research Institute-IRCCS, Troina, Italy; 3Department of Psychiatry and Psychotherapy, University of Münster, Münster, Germany; 4Department of Psychiatry, Melbourne Medical School, University of Melbourne, Parkville, VIC, Australia; 5The Florey Institute of Neuroscience and Mental Health, The University of Melbourne, Parkville, VIC, AustraliaCorrespondence: Alessandro Serretti, Email alessandro.serretti@icloud.comAbstract: Schizophrenia polygenic risk scores (SCZ PRS) have emerged as important tools for modulating factors not only in schizophrenia but also in major psychiatric disorders, such as major depression (MDD) and bipolar disorder (BD). Initially developed to capture the common variant risk for SCZ, accumulating evidence highlights the transdiagnostic impact of SCZ PRS on clinical severity, treatment response, and functional outcomes. This review synthesizes recent findings on the relationship between SCZ PRS and treatment outcomes across SCZ, BD, and MDD. A higher SCZ PRS is associated with poorer treatment outcomes, including treatment resistance or non-remission to antidepressants in MDD, reduced antipsychotic response in SCZ, and diminished lithium efficacy in BD. SCZ PRS is also linked to persistent negative symptoms, cognitive impairments, and long-term illness severity in SCZ. While the effect sizes are generally modest, integration of SCZ PRS with environmental factors, multiomics, and neuroimaging may enhance predictive accuracy. Despite variability in reported associations, the overarching evidence supports a transdiagnostic influence of SCZ PRS on disease trajectories and treatment responses. As a promising component of precision psychiatry, SCZ PRS holds potential for guiding more targeted and effective interventions. Future research should focus on combining SCZ PRS with multimodal approaches to fully realize its clinical utility.Keywords: schizophrenia, polygenic risk scores, major depressive disorder, bipolar disorder, treatment outcomes, precision psychiatry